Water quality mathematical modelling for drainage water in rural communities - El Gohary Rasha (Institut za istrazivanja i projektovanja u privredi, 2021)
The research's main objective is to study water quality management techniques using different scenarios by applying three mathematical models. The study focuses on the Rosetta Branch-River Nile, which is considered the supreme contaminated Branch of river Nile. The study is composed of three main parts. First: Water quality modeling using WASP 6 was adopted to simulate the water quality status. This model was calibrated and used to simulate different scenarios presenting an alternative solution for the water quality problem in Rosetta Branch. They also optimized water quality indicators using the genetic algorithm to determine the optimum techniques essential to eliminating the Rosetta branch's water quality problem. Second: Mathematical Modeling Using the SOBEK model, measure the environmental effect of wastewater discharges on the water quality of the Rosetta branch, taking into account seasonal variations. Third: statistical analyses to research the association between discharge and concentration of ammonia using simple regression equations. The study is focused on theoretical and applied scientific Methodology. It concluded that increased discharge in the Branch does not significantly affect water quality in the Branch. However, the treatment processes appear to have a large and significant impact on the water quality instead of increasing discharge solution. There is an inverse relationship between the discharge in Rosetta Branch and ammonia concentrations. All relationships have a correlation coefficient of, on average of about 0.7. The paramount water quality challenging in the Branch is cumulative of ammonia and Biological Oxygen Demand (BOD) overhead guidelines. Moreover, improving water quality for point source effluents, particularly at El Rahawy drain, improves the Rosetta branch's water quality.